Impact of Ciprofloxacin and Chloramphenicol on the Lipid Bilayer of Staphylococcus aureus: Changes in Membrane Potential. (23rd May 2013) - Páez, Paulina L.; Becerra, María C.; Albesa, Inés
Abstract : The present study was undertaken to explore the interaction of ciprofloxacin and chloramphenicol with bacterial membranes in a sensitive and in a resistant strains of Staphylococcus aureus by using 1-anilino-8-naphthalene sulfonate (ANS). The binding of this probe to the cell membrane depends on the surface potential, which modulates the binding constant to the membrane. We observed that these antibiotics interacted with the bilayer, thus affecting the electrostatic surface potential. Alterations caused by antibiotics on the surface of the bacteria were accompanied by a reduction in the number of binding sites and an increase in the ANS dissociation constant in the sensitive strain, whereas in the ciprofloxacin-resistant strain no significant changes were detected. The changes seen in the electrostatic surface potential generated in the membrane of S. aureus by the antibiotics provide new aspects concerning their action on the bacterial cell.